WINDOWS 10 – AT THE EDGE OF THE THEETS - Štambuk, Vladimir Z (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
Rarely, only once before, did Microsoft offer the public something for free. This time it is Windows 10 platform. The reasons are not altruistic. The reason is that in that way Microsoft is aiming to be, if not the only then, the dominant provider of computer platforms for the whole word. The fiasco with Windows 8 proved to be a iniciative to make Windows 10 free download for a period of one year. That period is now eanning out and Microsoft has to a large point sucsseded to emerge as a very important factor in PC and oxilery mashines, tas a dominant  factor. It shall remain so for years and will decide of the destiny of users almost autonomly.